Employee engagement in the South African short-term insurance sector: repositioning communication climate as a job resource - Annerie Geyer; Estelle De Beer (Communicare)
Measuring employee engagement is a popular means for contemporary organisations to assess employee commitment and engagement. It is evident from literature that a strong relationship exists between improved employee engagement levels and positive business outcomes. However, globally and in South Africa, employees tend not to be engaged, with non-managerial employees showing lower engagement compared to their managerial counterparts. From this perspective, disengagement, resulting in untapped employee potential, has significant financial implications.